Tracking the performance of world-ranked swimmers - Costa, M.J. (2011)
Tracking the swimming performance is important to analyze its progression and stability between competitions and help coaches to define realistic goals and to select appropriate training methods. The aim of this study was to track world-ranked male swimmer’s performance during five consecutive seasons (from 2003/2004 to 2007/2008) in Olympic freestyle events. An overall of 477 swimmers and 2385 season best performances were analyzed. FINA’s male top-150 rankings for long course in the 2007-2008 season were consulted in each event to identify the swimmers included. Best performances were collected from ranking tables provided by the National Swimming Federations or, when appropriate, through an internet database (www.swimranking.net). Longitudinal assessment was performed based on two approaches: (i) mean stability (descriptive statistics and ANOVA repeated measures, followed by a Bonferroni post-hoc test) and; (ii) normative stability (Pearson Correlation Coefficient and the Cohen’s Kappa tracking index). Significant variations in the mean swimming performance were observed in all events between all seasons. Performance enhancement was approximately 0.6 to 1 % between seasons leading up to the Olympics and approximately 3 to 4 % for the overall time-frame analyzed. The performance stability based on overall time-frame was moderate for all freestyle events, except in the 50-m (K = 0.39 ± 0.05) where it was low. Selfcorrelations ranged between a moderate (0.30 ≤ r < 0.60) and a high (r ≥ 0.60) stability. There was also a performance enhancement during all five seasons analyzed. When more strict time frames were used, the analysis of swimming performance stability revealed an increase in the third season. So, coaches should have a long term view in what concerns training design and periodization of world-ranked swimmers, setting the third season of the Olympic Cycle as a determinant time frame, due to performance stability until Olympic Games season.